Analysis of the vector control algorithm for new concept of Permanent Magnet Synchronous Machines in wide speed range - Klimkowski, Kamil; Gwozdziewicz, Maciej; Dybkowski, Mateusz (2017 International Symposium on Electrical Machines (SME), 2017)
In the paper the new concept of the Permanent Magnet Synchronous Machine (PMSM) is presented. This machine is based on classic construction of induction motor (IM). Parameterization and sweep analysis of the rotor geometry was done using the finite element analysis (FEA) software. Based on this analysis, one case was chosen and manufactured. In the paper the analysis of the new concept of the Permanent Magnet Synchronous Machines (PMSM) controlled by the vector control algorithm is presented and described. Drive is tested during different conditions. All results are performed by rapid prototyping card ds1103 coupled with the voltage inverter.